Codability of industry and occupation information from cancer registry records: Differences by patient demographics, casefinding source, payor, and cancer type. Issue 6 (25th March 2018) - Silver, Sharon R.; Tsai, Rebecca J.; Morris, Cyllene R.; Boiano, James M.; Ju, Jun; Scocozza, Marilyn S.; Calvert, Geoffrey M.
Abstract : Introduction: Industry and occupation (I&O) information collected by cancer registries is useful for assessing associations among jobs and malignancies. However, systematic differences in I&O availability can bias findings. Methods: Codability by patient demographics, payor, identifying (casefinding) source, and cancer site was assessed using I&O text from first primaries diagnosed 2011‐2012 and reported to California Cancer Registry. I&O were coded to a U.S. Census code or classified as blank/inadequate/unknown, retired, or not working for pay. Results: Industry was codable for 37% of cases; 50% had "unknown" and 9% "retired" instead of usual industry. Cases initially reported by hospitals, covered by preferred providers, or with known occupational etiology had highest codable industry; cases from private pathology laboratories, with Medicaid, or diagnosed in outpatient settings had least. Occupation results were similar. Conclusions: Recording usual I&O for retirees and improving linkages for reporting entities without patient access would improve I&O codability and research validity.